2002
DOI: 10.1108/14635780210446478
|View full text |Cite
|
Sign up to set email alerts
|

An international analysis of real estate journals

Abstract: The leading real estate journals in the USA, UK, Asia and Australia are analysed over 1991‐2000 to assess the impact of international real estate research in these journals. It is found that the focus on international real estate has expanded considerably in recent years, with this focus more evident in the leading UK real estate journals rather than the leading USA real estate journals. Reasons for this difference between the USA and UK real estate journals are identified. Issues relating to international aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Construction output research is predominantly published in construction management and real estate journals. In the field of construction management, an additional search was conducted on the databases of the following journals: The choice of these journals was informed by the following: (i) the ranking of the journal in the selected field (for details of ranking of construction management and real estate journals, refer to: Wing, 1997;Newell et al, 2002;and Hardin III et al, 2006);, and (ii) the number of relevant papers found in the journal at the end of the SCOPUS and WOS search. At the end of the second search (journal database search), 14 relevant articles were identified.…”
Section: The Search -(Pphase Ttwo Search)mentioning
confidence: 99%
“…Construction output research is predominantly published in construction management and real estate journals. In the field of construction management, an additional search was conducted on the databases of the following journals: The choice of these journals was informed by the following: (i) the ranking of the journal in the selected field (for details of ranking of construction management and real estate journals, refer to: Wing, 1997;Newell et al, 2002;and Hardin III et al, 2006);, and (ii) the number of relevant papers found in the journal at the end of the SCOPUS and WOS search. At the end of the second search (journal database search), 14 relevant articles were identified.…”
Section: The Search -(Pphase Ttwo Search)mentioning
confidence: 99%
“…A review manuscript co-sponsored by the Appraisal Institute and the American Real Estate Society recently appeared on the important topic of Real Estate Valuation Theory (edited by Wang and Wolverton, 2002). As far as international real estate research is concerned, several Special Issues of journals have appeared with a particular focus on international issues; for example, Real Estate Economics in 1995, the Journal of Real Estate Finance and Economics in 1993and 1997, the Journal of Real Estate Research in 1996and 1997, the Journal of Property Valuation and Investment in 1997 and the Journal of Property Research in 2000 (see Newell et al, 2002). Obviously, much research is still needed and this section provides some topics that would deserve further research.…”
Section: Towards a Research Agendamentioning
confidence: 99%
“…Both these studies made use of only the respondents' perception by way of questionnaires that were analysed and were limited to US journals. Newell et al (2002) investigated the performance of international journals and found the Pacific Rim Property Research Journal (PRPRJ) to be the leading Australian journal. The study investigated the internationalisation of research by comparing origin of authors to origin of journal and ranking top authors in the USA and UK journals.…”
Section: Introductionmentioning
confidence: 99%
“…From the above, it is evident that most previous research on journal preferences and other related research on real estate research performance focussed primarily on US journals and researchers, except for research by Newell et al (2002), Newell (2003) and the study by Worzala and Tu (2010). Furthermore, there is a common research basis of using questionnaires to obtain authors' perceptions or to investigate publications to measure performance of individuals or institutions and to identify the main topics that are being researched.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation